PEMANFAATAN MEDIA SOSIAL WHATSAPP SEBAGAI MEDIA KOMUNIKASI DALAM SISTEM KERJA REMOTE WORKING (Studi Kasus Pada Pt. Quattro Media Contindo Selama Masa Pandemi Covid-19) - Muhammad Naufal Ramadhan (2020)
Advances in technology have led to a variety of new media as a medium of communication. Social media began to be used as a support system for remote working. Since the beginning of March 2020, PT. Quattro Media Contindo implements remote working because of the government's PSBB policy due to the corona virus pandemic. The social media used is WhatsApp. The theory used in this research is Computer Mediated Communication (CMC) Theory. Data collection techniques with interviews with 3 employees of PT. Quattro Media Contindo and documentation come from screenshots and the internet. The research results obtained are on the use of WhatsApp social media, activities carried out include receiving and sending documents and communicating with related parties by utilizing the chat feature, sending documents, voice and video calls, and group video calls. In supporting factors, there is a desire for work to be better, ease of communication with related parties, and ease of use of features. In the inhibiting factor, there are technical, external, and related individual factors.